E-Waste Management Scenarios in Malaysia. (29th September 2014) - Suja, Fatihah; Abdul Rahman, Rakmi; Yusof, Arij; Masdar, Mohd Shahbudin
Abstract : e-Waste, or electronic waste, disposal that is uncontrolled can be harmful to human health and the environment because e-waste contains toxic substances and heavy metals. However, if the waste is properly managed, it can become a business opportunity that produces high returns because e-waste also contains valuable materials, such as gold, silver, platinum, and palladium. The government of Malaysia wants to ensure the safe, effective, and economically beneficial management of e-waste in Malaysia. Management approaches have included law enforcement and regulation and the promotion of e-waste recovery activities. e-Waste of no commercial value must be disposed of at sites/premises licensed by the Department of Environment (DOE), Malaysia. To date, 18 full recovery facilities and 128 partial recovery facilities that use various available technologies have been designated for the segregation, dismantling, and treatment of e-waste. However, there are issues faced by the recovery facilities in achieving the goal of converting e-waste into a source material. The issues include the e-waste supply, the importation of e-waste derived products and coding, and finally the need to develop the criteria for e-waste processing technologies to ensure the safety and the sustainability of the facilities.